Pizza and Taco : best Christmas ever! - Shaskan, Stephen (Shaskan, Stephen. Pizza and Taco, 2024)
Best friends Pizza and Taco prepare for Christmas by making their wish lists and doing good deeds to get on Santa Slaw's Nice List.